Intersectionality and women's access to justice in Africa - Dawuni, J. Jarpa; Sebutinde, Julia, 1954- (Lanham: Lexington Books, 2022)
"This book examines women's access to justice in both traditional and statutory courts through an intersectional lens. It analyzes the lived experiences of women and their access to justice by situating the courtroom as both a spatial and a temporal arena for seeking justice (as litigants) and for seeking access to the bench (as judges)"--
Introduction -- Layered intersectionality and framing feminist legal discourse on access to justice for women / J. Jarpa Dawuni -- Status of women judges in Algeria : achievements and pathways for the future / Samia Bourouba -- Opening the door for women in the Cape Verdean judiciary / Justice Vera Duarte -- Women judges in Ethiopia / Maame Efua Addadzi-Koom and Biruh Gemeda Gage -- Battle for women in the Egyptian judiciary : reality, laws, and aspirations or a dream come true? / Omnia Taher Gadalla -- Making gains for women's rights : using gender quotas to achieve gender equality in the composition of the Supreme Court of Kenya / Annerita Murungi and Agnes Meroka-Mutua -- "Your whole life is an interview to get to the bench" : gender and judicial appointments in Malawi / Rachel Ellett -- Gender transformation of the judiciary in South Africa justice / Constance Baratang Mocumie -- A critical assessment of the status of women judicial officers in Uganda / Josephine Ndagire -- Women's property rights and discriminatory land tenure systems in Ghana : the adjudicative role of courts / Michael Addaney -- The making and unmaking of gender : reflections on questions of gender and the judiciary in Namibia / Kennedy Kariseb -- Women and environmental justice issues in Nigeria : an evaluation / Eghosa Ekhator and Pedi Obani -- Contribution of the judiciary to the advancement and protection of women's matrimonial and inheritance rights in Rwanda / Marie-Rose Turamwishimiye and Odette Uwineza -- Gender and customary justice among the Podoko of the Mandara mountains of the far north region of Cameroon / Jeremie Diye -- Juxtaposing the efficacy of testacy and intestacy to inheritance rights for Rukuba widows and children under Nigeria's Plural Legal System / Rebecca Badejogbin and Vicki Lawal -- Transforming traditional justice through gender diversification : comparing two South African communities / Sindiso Mnisi Weeks -- Intersectionality, access to justice and women's experiences : policy recommendations / J. Jarpa Dawuni and Stephen Muthoka Mutie.
Includes bibliographical references and index.
Keywords: Women -- Legal status, laws, etc. -- Africa; Sex discrimination in justice administration -- Africa; Intersectionality (Sociology)